AN ANALYSIS OF TYPES OF ONOMATOPOEIA IN “ONE-PIECE” MANGA - Dinata, I Putu Indra; Juniartha, I Wayan (Yavana Bhasha : Journal of English Language Education, 2024)
This research is an analysis of the types of onomatopoeia in "One-Piece" manga. This research aims to educate readers about the fact that not all comics from around the world use the same word and that each comic from each country uses a unique one. This research uses descriptive qualitative approaches to analyze data to identify issues with the use of the word onomatopeia present in one-piece comics based on the theory of types by Elizabeth (2013), and both formal and informal methods are used to present the findings. Observation and documentation methods were used in this research which conducted 4 techniques in collecting the data, they are: watching, note-taking, selecting, and classifying. The results of this research show that there is a significant cultural variation in the way the word is used in comics, and each culture has a different perception of these sounds. In observing this variation, readers can understand how significant cultural factors are in shaping linguistic expressions, as well as how language develops and adapts in the context of diverse societies. Keywords: onomatopoeia, manga, type of onomatopoeia